2022
DOI: 10.1186/s40854-021-00327-0
|View full text |Cite
|
Sign up to set email alerts
|

Non-Value-Added Tax to improve market fairness and quality

Abstract: The promotion of both market fairness and efficiency has long been a goal of securities market regulators worldwide. Accelerated digital disruption and abusive trading behaviors, such as the GameStop mania, prompt regulatory changes. It is unclear how this “democratization” of trading power affects market fairness as economies cope with pandemic-driven shifts in basic systems. Excessive speculation and market manipulation undermine the quality of financial markets in the sense that they cause volatility and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 68 publications
(84 reference statements)
0
1
0
Order By: Relevance
“…Conversely, Stiglitz (1989), Eichfelder and Lau (2017) found that transaction taxes can reduce volatility and improve efficiency. Veryzhenko, et al (2022) propose a Non-Value-Added Tax that taxes profitable transactions not supported by fundamentals, which they claim could enhance market efficiency. In summary, while certain measures show potential, the evidence is mixed on whether and how regulations like trading halts, price limits and taxes ultimately improve stock market efficiency.…”
Section: Ways To Improve Stock Market Efficiency: a Reviewmentioning
confidence: 99%
“…Conversely, Stiglitz (1989), Eichfelder and Lau (2017) found that transaction taxes can reduce volatility and improve efficiency. Veryzhenko, et al (2022) propose a Non-Value-Added Tax that taxes profitable transactions not supported by fundamentals, which they claim could enhance market efficiency. In summary, while certain measures show potential, the evidence is mixed on whether and how regulations like trading halts, price limits and taxes ultimately improve stock market efficiency.…”
Section: Ways To Improve Stock Market Efficiency: a Reviewmentioning
confidence: 99%